Synthesis, structural, morphological and optical properties of (ZnO)x(TiO₂)₁-x nanoparticles prepared through thermal treatment technique - Muhamad, Suzliana (2020)
Numerous studies have researched the chemical, physical, and photochemical characteristics of zinc oxide titania ZnO-TiO2 nanoparticles resulting through various routes of fabrication. The properties of nanoparticles rely upon the chemical composition and microstructural features in which the shape and the particle size might be controlled in the preparation procedure. Several techniques have been applied previously to create ZnO-TiO2 nanoparticles with potential physical and chemical properties. However, no previous research has been found in utilizing thermal treatment method to convey ZnO-TiO2 nanoparticles. Relative to most other techniques, thermal treatment method has a more straightforward methodology, shorter reaction time, lower reaction temperature, utilize less number of synthetic substances, does not utilize any toxic reagent and furthermore does not produce earth unsafe waste. In this thesis, the current study applied thermal treatment method to synthesize (ZnO)x(TiO2)1−x nanoparticles with x = 0.25, 0.50 and 0.75 by using only metal precursors (zinc nitrate and titanium (IV) propoxide), capping agent polyvinylpyrrolidone (PVP) and deionized water. The aqueous solution containing the metal precursors, the capping agent PVP and deionized water was dried for 24 hours at 80 C, ground to turn out to be fine powder and lastly calcined at temperature ranging from 500 to 800 C. The structural, morphological and optical properties of the synthesized samples were examined by utilizing different characterizations such as X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) spectroscopy, ultraviolet-visible (UV-Vis) spectrophotometry and photoluminescence (PL) spectroscopy. Likewise, thermogravimetric analyzer (TGA) was used to study the thermal stability and to determine the ideal calcination temperature at which polymer could be removed from the samples. The TGA measurement demonstrated that the capping agent PVP was completely deteriorated at temperatures higher than 500 C which is in concurrence with the vanishing of PVP absorption peaks in the FTIR spectra. XRD spectra of the nanoparticles that have been calcined at 500−800 °C uncovered that the mean crystallite size for (ZnO)x(TiO2)1−x nanoparticles were in the range of 24.90 to 92.82 nm with the structure of hexagonal zinc oxide, tetragonal titania, hexagonal ecandrewsite and cubic titanium dizinc oxide. The XRD results were additionally affirmed by TEM analysis which confirmed the development of nanoscale samples. As the calcination temperature increased, the average nanoparticle size determined through TEM image also increased from 25.922 to 90.056 nm. Furthermore, the optical behavior of the prepared nanoparticles was considered by means of UV-Vis spectrophotometer whereby the optical band gaps were determined by using Kubelka-Munk equation. The various band gaps showed up in the absorption spectra essentially demonstrated an increasing trend ranging from 3.238 to 3.741 eV as the calcination temperature increased from 500 to 800 °C. PL spectral investigations of the nanoparticles demonstrated emission peaks at around 420 nm (violet) and 480 nm (blue) for an excitation wavelength of 280 nm. The procured information on the synthesized (ZnO)x(TiO2)1−x nanoparticles through thermal treatment method propose that the samples have extraordinary potential in semiconductor applications, for example, photocatalytic and wide band gap power devices.